Haiti and its multiple tragedies: Much more needs to be done - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2022)
Haiti has been suffering for many decades a damaging combination of climate and natural disasters and political, economic, social, and health crises. Just in the last months there was the terrible assassination of a sitting president on July 2021; an extremely damaging earthquake of 7.2 magnitude on August 2021; the heart-wrenching images of Haitians at the US-Mexican border in September 2021; the expansion of gang activity with the kidnapping of US missionaries in October 2021; the more recent alarming episode of the shooting at the current interim Prime Minister in January 2022; and another earthquake of 5.3 magnitude in late January, to name only the more recent sequence of very bad events affecting the country.